Charge-balanced biphasic electrical stimulation inhibits neurite extension of spiral ganglion neurons. (15th June 2016) - Shen, Na; Liang, Qiong; Liu, Yuehong; Lai, Bin; Li, Wen; Wang, Zhengmin; Li, Shufeng
Highlights: We design a system of SGN dissociated culture under CI electrical stimulation. CI electrical stimulation inhibits SGN neurites extension. CI electrical stimulation reduces Schwann cell density in vitro . Inhibiting calcium influx through VDCCs reduces electrical stimulation's effect. Abstract: Intracochlear application of exogenous or transgenic neurotrophins, such as neurotrophin-3 (NT-3) and brain derived neurotrophic factor (BDNF), could promote the resprouting of spiral ganglion neuron (SGN) neurites in deafened animals. These resprouting neurites might reduce the gap between cochlear implant electrodes and their targeting SGNs, allowing for an improvement of spatial resolution of electrical stimulation. This study is to investigate the impact of electrical stimulation employed in CI on the extension of resprouting SGN neurites. We established an in vitro model including the devices delivering charge-balanced biphasic electrical stimulation, and spiral ganglion (SG) dissociated culture treated with BDNF and NT-3. After electrical stimulation with varying durations and intensities, we quantified neurite lengths and Schwann cell densities in SG cultures. Stimulations that were greater than 50 μA or longer than 8 h significantly decreased SG neurite length. Schwann cell density under 100 μA electrical stimulation for 48 h was significantly lower compared to that in non-stimulated group. These electrical stimulation-induced decreases of neurite extension and Schwann cell density were attenuated by various types of voltage-dependent calcium channel (VDCC) blockers, or completely prevented by their combination, cadmium or calcium-free medium. Our study suggested that charge-balanced biphasic electrical stimulation inhibited the extension of resprouting SGN neurites and decreased Schwann cell density in vitro . Calcium influx through multiple types of VDCCs was involved in the electrical stimulation-induced inhibition.